Café-concert and music hall gestures in Soviet silent adventure films / Жестовая система кафе-концертов и мюзик-холлов в советском немом приключенческом фильме - DARIA O. MARTYNOVA / Д. О. МАРТЫНОВА (Наука телевидения)
This paper examines how the characteristic behaviors of late 19thand early 20th-century café-concerts and music halls shaped the portrayal of women in post-revolutionary Soviet silent cinema. While some Russian scholars have noted the relative neglect of performer imagery during this period, the present study hypothesizes that some female performers in these films symbolized the vices of the “old world” or highlighted the corruption around them, while others represented the “new woman,” reinforcing Soviet ideals. These “imperfect” dancers, through their movements and poses, either heightened the positive qualities of the perfect Soviet hero or created a stark contrast. The primary focus is on Evil Spirit, analyzed here for the first time, along with The Happy Canary and The Bear’s Wedding. For comparative purposes, the study also includes The Doll with Millions, The Ice House, and The Devil’s Wheel. Furthermore, Soviet films are compared to French and German silent films from the 1910s and 1920s, which similarly employed cabaret and variety show imagery. The study concludes that cabaret and its performers served as both the setting and the means (locus and modus agendi) for criticizing prerevolutionary morals and highlighting the positive aspects of the “new Soviet man.”